Justice for all : how the Jewish Bible revolutionized ethics - Unterman, Jeremiah (Philadelphia : Jewish Publication Society ; Lincoln : University of Nebraska Press, 2016)
"Demonstrates how the Jewish Bible radically changed the course of ethical thought and as a result has had enormous influence on later Jewish thought and law, as well as on Christianity and the development of modern Western civilization"--
1. The Jewish Bible's unique understanding of God: the ethical relationship of God to the world and humanity -- 2. The revelation at Sinai: ethical implications of the God-Israel relationship -- 3. Providing for the disadvantaged: the stranger, the poor, the widow, and the orphan (with a note on slavery) -- 4. The primacy of morality over ritual: a prophetic innovation -- 5. The requirement of "Return": the development of repentance from Torah to prophecy (with a note on theodicy) -- 6. The establishment of hope: the prophetic promise of redemption.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072
Keywords: Bible. -- Criticism, interpretation, etc; Ethics in the Bible; Jewish ethics -- Biblical teaching; RELIGION / Judaism / General; RELIGION / Judaism / History; Electronic books